The Role of Leadership Style on Turnover Intention - Maaitah, Ayman Mahmoud (International Review of Management and Marketing, 2018)
This research aims at exploring the effect of transformational leadership and transactional leadership on the turnover intention for directors of the Greater Amman Municipality directorates; an Analytical, descriptive method has been applied and utilised. Research population was chosen from directors of the Greater Amman Municipality departments and heads of sections, where the number of the population was 602, and a simple random sample was chosen, which equal to 274 responds , the researcher relied on questionnaires as the primary tool to collect data, 190 surveys were received back and 18 questionnaire were canceled because of the lack of their suitability for statistical analysis, this results in 172 valid questionnaires which represent 62.7% as a response rate for this study, The results find out also that there is a statistically significant impact for the transformational leadership and transactional leadership on substantial level to affect turnover intention from directors of Greater Amman Municipality department's point of view. The study concludes some points, most of them are: more research and field studies must be undertaken to identify the importance of transformational and transactional leadership in achieving Greater Amman municipality ‘s resent and future objectives, more attention must be paid for those directors in Greater Amman municipality who seem to have the attributes and characteristics of transformation leadership, and also those who have the ability and required skill to develop human resources in Greater Amman Municipality, giving more trainings and special workshops to build leaders and train them on modern administrative methods in order to improve their abilities, performance and encourage them to provide the best they have. Keywords: transformational leadership, transactional leadership, turnover intention JEL Classifications: G1, G12 https://doi.org/10.32479/irmm.6859